Barriers to Women’s Gaining a Role in Grassroots Government: The Case of a Questionnaire Survey of Grassroots Civil Servants in China - Wenru Mo (Studies in Social Science & Humanities, 2024)
This dissertation investigated the barriers faced by female civil servants in grassroots government in China when it comes to work and promotion. On the basis of the existing literature, three research questions are posed in this dissertation:1) Do women face barriers when seeking access to local government? If so, what are these barriers? 2) Does gender socialisation and gender norms have an impact on women’s representation in government? 3) What are the career goals of women entering government at the primary level? To address these research questions, this dissertation used mixed methods research methodology, which employed a non-quantitative questionnaire to collect data. To ensure the accuracy of the final questionnaire, this dissertation conducted a Pilot Study to get feedback from the target people. According to findings and discussion, this dissertation found that traditional Chinese gender norms and gender-based discrimination, including internalised sexism constrain the job development of female civil servants at the primary level. It also found that the weakness of China’s elderly care facilities makes daughters-in-law the primary bearers of elderly care responsibilities, which can place additional family burdens on grassroots women and discourage their job advancement. The study further found that the patriarchal dominant ‘guanxi’ culture is unfair to the development of female civil servants at the grassroots level. This dissertation mainly reveals the restrictions and barriers imposed on women under the patriarchal culture.